Ultrasonic and Spectral Studies on Hydrogen Bonded Complexes of Aromatic Aldehydes and N-Methylaniline in n-Hexane - Kumar, R.; Santhi, B.S.; Mr., Vijayakanth; Kannappan, V. (Journal of Applied Solution Chemistry and Modeling, 2013)
Ultrasonic and UV-spectral studies have been carried out for three ternary systems containing N-methylaniline (NMANI) and three structurally different aromatic aldehydes, benzaldehyde (BA), cinnamaldehyde (CA) and salicylaldehyde(SA) in n-hexane medium at 303.15 K and at atmospheric pressure. Acoustical parameters are computed from the measured values of ultrasonic velocity, density and dynamic viscosity. The variation of acoustical parameters in the concentration range investigated establishes complex formation through intermolecular hydrogen bonding between aldehyde and N-methylaniline. The existence of strong aldehyde-amine interaction is also confirmed through the recorded UV-Visible absorption spectra with Benesi-Hildebrand theory at 303.15 K. The formation constants of the hydrogen bonded complexes are determined by spectroscopic and ultrasonic methods and compared. These values computed by two different methods are comparable and follow similar trend. The trend in the formation constants is discussed based on structures of the component molecules and correlate with computed molecular properties